KARAKTERISTIK SAMPAH DAN PERSEPSI MASYARAKAT TERHADAP PENGELOLAAN SAMPAH DI KECAMATAN BANYUWANGI KABUPATEN BANYUWANGI PROVINSI JAWA TIMUR - Shinta E. Maharani; I Wayan Suarna; I W. Budiarsa Suyasa (Master Program of Environmental Science, Postgraduate Program of Udayana University)
This study concern waste characteristics and community’s perception of waste management inBanyuwangi District, Banyuwangi Regency, East Java Province. It was conducted in February up to August2006. It aims to (1) know waste characteristics in the Bulusan Final Disposal Area (TPA) in the service areaof Banyuwangi District compared with that in the service area of Kalipuro District, Banyuwangi Regency,(2) know the perception and role of the component of waste producers that cover household, tourismsupporting industry, and government institution having the authority in waste management in BanyuwangiDistrict, Banyuwangi Regency, East Java Province to waste management in determining the pattern of its management, and (3) know the alternative of the suitable pattern of waste management to be applied inBanyuwangi Regency and the surrounding areas.The study was conducted with direct observation to the TPA Bulusan, distributing questionnaire, andconducting direct interview with some government institutions that deal with the service of wastemanagement. The questionnaire data to get the community’s perception were analyzed by means of forcefieldanalysis to obtain the positive and negative value of the existing problems.The findings show that (1) Banyuwangi District has the biggest percentage of organic wastecharacteristics spread among other wastes such as plastic, paper, textile, and glass waste, (2) socio-economicfactor of the household waste has the highest positive value compared with the component of tourismsupporting and government institution. Banyuwangi Regency’s community’s perception as a whole haspositive value and support the effort by finding a better solution to the problem, and (3) the suitablealternative of the pattern of waste management to be applied in Banyuwangi District and the surroundingareas is the development of human resources, the addition of educational curriculum, economicimprovement, the improvement of facilities and infrastructure, introduction of local regulations, and theforming of media for the community.